Giant sigmoid diverticulum. - López, Daniel; Mori, Raúl; Schneeberger, Federico; Gómez Fossati, Carlos (Cirugía del Uruguay, 1987)
A case of giant sigmoíd diverticulum that hada rectal haemorrhage and was diagnosed by a barium enema is presentad. Frecuents symptoms and habitually used diagnostlc procedures are remarked. Considerations about pathology and treatment are done. Preferené:e for segmentary colectomy with primary anastomosis is expressed.